Fluctuation Suppression to Optimize Initial Data to Increase the Quality of Truncation Approximants in Probabilistic Evolution Approach for ODEs: Basic Philosophy - (:unkn) unknown (AMER INST PHYSICS, 2012)
This work focuses on initial fluctuation optimization on truncation approximants of Probabilistic Evolution for Ordinary Differential Equations (ODEs). Probabilistic Evolution Approach (PEA) is a new method which is proposed by Metin Demiralp and his group (Group of Science and Methods of Computing). This approximation enables us to convert nonlinear differential equations to linear ones.
Keywords: Fluctuation Optimization; Truncation; Probabilistic Evolution; Probabilistic Evolution Approach (PEA); Evolution Matrix; Ordinary Differential Equation (ODE)